(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
The contribution reflects on the concrete modalities through which Vittorio Alfieri took care of the printing of his own works. The main features of Alfieri’s activity before, after and during the printing of the volumes are analysed, reconstructing the different publishing stages of his literary career, from the first Sienese printing of the tragedies to the definitive printing by Didot, passing through the clandestine edition of the political works in Kehl. In this way, an attempt is made to highlight the theoretical and poetic implications underlying Alfieri’s printing practice.